1963
DOI: 10.1037/h0045307
|View full text |Cite
|
Sign up to set email alerts
|

Maternal behavior in the domestic hen: The role of physical contact.

Abstract: In 3 experiments the development of broodiness was studied in relation to restriction of physical contact between hen and chicks. Compared to control Ss, significantly fewer experimental Ss developed broodiness when isolated from physical contact with chicks by confinement in cages adjacent to chicks or above chicks (presumably normal position for brooding) and when contactual ventral surface of Ss was anesthetized to eliminate contact cues. In 3 parallel experiments on the maintenance of broodiness, it was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1963
1963
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…These results are consistent with previous data showing that maternal responses emerged gradually during sensitization experiments in hens (e.g. The crucial role of ventral tactile contact of the hen with her young in relation to appearance and maintenance of hen maternal behaviour has been previously emphasized (3,6). However, there was an appreciable lag in close proximity and maternal calling for hens maintained with older chicks over the first three days compared with hens maintained with younger ones.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous data showing that maternal responses emerged gradually during sensitization experiments in hens (e.g. The crucial role of ventral tactile contact of the hen with her young in relation to appearance and maintenance of hen maternal behaviour has been previously emphasized (3,6). However, there was an appreciable lag in close proximity and maternal calling for hens maintained with older chicks over the first three days compared with hens maintained with younger ones.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this experiment confirm previous reports (11,14) that it is possible to induce a rapid onset of maternal responses in hens outside their normal reproductive cycle. However, it is evident that the experimental situation influences the appearance of these responses.…”
Section: Discussionsupporting
confidence: 90%
“…darkness, restricted space), and agrees with experimental results showing the crucial role of ventral tactile stimulation in the establishment of maternal behaviour (11,15). darkness, restricted space), and agrees with experimental results showing the crucial role of ventral tactile stimulation in the establishment of maternal behaviour (11,15).…”
Section: Discussionsupporting
confidence: 90%
“…A preliminary study (Maier, 1962) indicated that development of broodiness was not affected by manipulating pretest experience. However, observations suggested that the hen's choice of chicks to brood was influenced.…”
Section: Methodsmentioning
confidence: 99%